Removal of lead from waste oil using ultrasound assisted with rice bran - Norhafzan, Junadi (2010)
Heavy metal ion such as lead is toxic and represent as hazardous pollutants due to its persistent in the environment. In this study the rice bran was used for the sorption of lead from waste lubricant oil in the presence and absence of ultrasound. The main objective of this study is to get the optimum condition towards lead removal from waste oil in the presence and absence of ultrasound. The effect of temperature, particle size and adsorbent dosage on removal of lead was investigated. Temperatures of solutions and adsorbent dosage were varied from 40 - 90 oC and 1 – 6 g/100 mL, respectively while the particle size of rice bran were prepared in the range of 0 – 200, 400 -500 and 630 - 800 μm. From the result obtained, the optimal temperature of solution for highest adsorption of lead were 80 °C and 90 °C, respectively, in the presence and absence of ultrasound. Of the particle sizes studied, 0 – 200 μm of rice bran exhibited the highest adsorption capacities and in adsorbent dosage studies, the results indicated that the adsorption process reached equilibrium after 4 g/100 mL in presence and absence of ultrasound. The results of this study showed that higher lead adsorption was observed at higher temperature, smaller particle size and larger adsorbent dosage. In the presence of ultrasound the rice bran was a more efficient sorbent for lead sorption than its absence. The effect of ultrasound on the sorption process could be explained by the thermal and non-thermal properties of ultrasonic field. As conclusion, ultrasound was synergetic with rice bran as adsorbent when they were used together to extract heavy metals from waste oil.